MicroRNA Profile of MA-104 Cell Line Associated With the Pathogenesis of Bovine Rotavirus Strain Circulated in Chinese Calves - Elkady, Gehad; Chen, Yingyu; Hu, Changmin; Chen, Jianguo; Chen, Xi; Guo, Aizhen (Frontiers in Microbiology, 2022)
Bovine rotavirus (BRV) causes massive economic losses in the livestock industry worldwide. Elucidating the pathogenesis of BRV would help in the development of more effective measures to control BRV infection. The MA-104 cell line is sensitive to BRV and is thereby a convenient tool for determining BRV–host interactions. Thus far, the role of the microRNAs (miRNAs) of MA-104 cells during BRV infection is still ambiguous. We performed Illumina RNA sequencing analysis of the miRNA libraries of BRV-infected and mock-infected MA-104 cells at different time points: at 0 h post-infection (hpi) (just after 90 min of adsorption) and at 6, 12, 24, 36, and 48 hpi. The total clean reads obtained from BRV-infected and uninfected cells were 74,701,041 and 74,184,124, respectively. Based on these, 579 were categorized as known miRNAs and 144 as novel miRNAs. One hundred and sixty differentially expressed (DE) miRNAs in BRV-infected cells in comparison with uninfected MA-104 cells were successfully investigated, 95 of which were upregulated and 65 were downregulated. The target messenger RNAs (mRNAs) of the DE miRNAs were examined by bioinformatics analysis. Functional annotation of the target genes with Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) suggested that these genes mainly contributed to biological pathways, endocytosis, apoptotic process, trans-Golgi membrane, and lysosome. Pathways such as the mammalian target of rapamycin (mTOR) (mml-miR-486-3p and mml-miR-197-3p), nuclear factor kappa B (NF-κB) (mml-miR-204-3p and novel_366), Rap1 (mml-miR-127-3p), cAMP (mml-miR-106b-3p), mitogen-activated protein kinase (MAPK) (mml-miR-342-5p), T-cell receptor signaling (mml-miR-369-5p), RIG-I-like receptor signaling (mml-miR-504-5p), AMP-activated protein kinase (AMPK) (mml-miR-365-1-5p), and phosphatidylinositol-3-kinase/protein kinase B (PI3K/Akt) signaling (mml-miR-299-3p) were enriched. Moreover, real-time quantitative PCR (qPCR) verified the expression profiles of 23 selected DE miRNAs, which were consistent with the results of deep sequencing, and the 28 corresponding target mRNAs were mainly of regulatory pathways of the cellular machinery and immune importance, according to the bioinformatics analysis. Our study is the first to report a novel approach that uncovers the impact of BRV infection on the miRNA expressions of MA-104 cells, and it offers clues for identifying potential candidates for antiviral or vaccine strategies.